Cuidado e precariedade em Anna Tsing e Maria Puig de la Bellacasa - Ferreira, Amanda Finotti Lagos (Universidade Federal de São Carlos, 2023)
Maria Puig de la Bellacasa and Anna Tsing are authors who work with multispecific ethnographies focused on the problem of the Anthropocene. Although with different backgrounds and in dialogue with different theoretical traditions, this article seeks to shed light on possible complementarities between their works. While Tsing is interested in following the trails of matsutake mushrooms and their foragers on the precarious edges of the capitalist system, Puig de la Bellacasa puts posthumanist and feminist thought into dialogue to think about how an ethic of care is made in practice in a community of permaculture. Based on the concept of “landscape” (Ingold, 1993; Tsing, 2015, 2019, 2022), this article seeks to i. demonstrate the similarities and distances between the ethnographies of both authors, ii. to think about the problem of human co-implication in different landscapes and iii. to present an elaboration on the possible relationships between precarity and care based on their ethnographic data.
Care and precarity in Anna Tsing and Maria Puig de la Bellacasa
Keywords: Cuidado; Precariedade; Paisagem; antropoceno; Etnografia multiespecífica; Care; Precarity; Landscape; Anthropocene; Multispecific ethnography; CIENCIAS HUMANAS::ANTROPOLOGIA::TEORIA ANTROPOLOGICA